2021
DOI: 10.3389/fgene.2021.632385
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Genome-Wide Polygenic Score Model for Predicting the Risk of Type 2 Diabetes

Abstract: Polygenic risk score (PRS) has been shown to be predictive of disease risk such as type 2 diabetes (T2D). However, the existing studies on genetic prediction for T2D only had limited predictive power. To further improve the predictive capability of the PRS model in identifying individuals at high T2D risk, we proposed a new three-step filtering procedure, which aimed to include truly predictive single-nucleotide polymorphisms (SNPs) and avoid unpredictive ones into PRS model. First, we filtered SNPs according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
1
20
0
2
Order By: Relevance
“…Interest in PRS to assess clinical risk for complex disorders has gained traction over the past several years, with PRSs having been developed for cancer risk, 70 , 71 , 72 CAD, 22 and diabetes. 22 , 73 One area that has had limited uptake of PRSs is a field that has a long history of genetic and genomic testing for rare congenital syndromes: clinical genetics. The classic population in medical genetics has been children with rare, phenotypically classifiable, genetic syndromes caused by single-gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in PRS to assess clinical risk for complex disorders has gained traction over the past several years, with PRSs having been developed for cancer risk, 70 , 71 , 72 CAD, 22 and diabetes. 22 , 73 One area that has had limited uptake of PRSs is a field that has a long history of genetic and genomic testing for rare congenital syndromes: clinical genetics. The classic population in medical genetics has been children with rare, phenotypically classifiable, genetic syndromes caused by single-gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on CAD, T2D, atrial fibrillation, breast and prostate cancer found that PRS improved the prediction power of such predictors [ 36 ]. Similarly, augmenting PRS with additional information such as BMI, and lab results such as HDL and LDL measures improved prediction power for T2D [ 37 ]. Similarly, augmenting PRS by traditional measures for cardiovascular disease risk modestly enhanced its prediction power [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…При помощи ШГР оценивалось влияние генетической предрасположенности к ожирению на продолжительность жизни. Интересно, что высокие показатели ШГР ожирения имели значительное влия-ШГР СД [31]. Анализ генетических данных 274029 участников показал, что тщательный отбор ВНП позволяет разрабатывать шкалы риска, которые обладают достоверной прогностической цен ностью (площадь под кривой (AUC)=0,795; 95% ДИ: 0,790-0,800).…”
Section: шгр метаболических нарушений и персонализированная профилактикаunclassified